Strain Variation in NbTi Filaments - Luhmann, Jason D. (My University, 2013)
NbTi superconducting wires are used in a wide variety of magnet systems to carry large electric currents and produce large magnetic fields of 1 - 5 T. These wires, consisting of NbTi filaments located within the host Cu wire, need to perform at engineered levels for optimal performance of the device. To do this, the wires are drawn to carefully-specified levels of strain, which causes precipitation of an [alpha]-Ti phase that dramatically improves the current-carrying capacity of the superconductor. To assess how uniformly the strain is being applied to NbTi filaments within a composite wire, an image analysis technique was developed to identify geometrical variations among filaments in a wire and between wires from different starting billets. The purpose of this study was to use scanning electron microscopy (SEM) to perform the image analysis on two separate billets of the same initial design.
Color poster with text, photographs, images, tables, and charts.
Keywords: Scanning electron microscopy; Niobium-titanium; Superconducting wire; Posters